Faktor-Faktor Yang Mempengaruhi Pendapatan Petani Cengkeh Di Desa Munduk Kecamatan Banjar Kabupaten Buleleng - Marpilina, Luh Lidya; Sudiana, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
The purpose of research, to determine the influence of labor, technology and production simultaneously and partially to the income of clove farmers in the Village Munduk Banjar District Buleleng. The population of this study were 70 clove farmers by stratified random sampling. The analytical technique used to is multiple linier regression analysis. The result of analysis shows that labor, technology, production quantity have positive and significant influence simultaneously to clove farmer's income in Munduk Village, Banjar Sub-district, Buleleng Regency. Labor has a positive and partially significant effect on the income of clove farmers in Munduk Village, Banjar District, Buleleng District. Technology negatively affected partially to the income of clove farmers in the Village Munduk Banjar District Buleleng District. The number of production has a positive and significant effect partially on the income of clove farmers in Munduk Village, Banjar District, Buleleng District.